Policy Smart Card 1.0 / Farah Amirah Fuad, Muhammad Faris Amirul Fuad and Mohammad Aminy Md Nazim - Fuad, Farah Amirah; Fuad, Muhammad Faris Amirul; Md Nazim, Mohammad Aminy (2021)
As per the Industrial Revolution 4.0 (IR4.0) requirements, the educational system has transformed the learning process into technology-based learning to meet 21st-century learning needs. Recognizing the relevance of modern technology, such as QR codes, to the community, especially students, the idea for a Policy Smart Card (PSC 1.0) was formed. PSC 1.0 contains a QR code that directs users to a custom- built website containing Malaysian government policies. While the objective of this PSC 1.0 is to ensure that receiving information is practicable, could save time, and spread awareness and knowledge among people, especially students nowadays. The commercialization target of PSC 1.0 is students, particularly policy students, as well as lecturers. It is also expected to be benefits such as resources for the public.